2010
DOI: 10.1007/s00497-010-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation during sexual embryogenesis and implications on the induction of somatic embryogenesis in Castanea sativa Miller

Abstract: From anthesis to mature seed formation, burrs from cross-pollinated adult Castanea sativa Miller trees were characterized and seven developmental stages defined based on macro and micromorphological traits. In order to get an insight into the involvement of epigenetic mechanisms in sexual embryogenesis and to define somatic embryogenesis induction capability, global DNA methylation and the somatic embryogenic competence were quantified. On cross-pollinated trees once fertilization takes place, at least one ovu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 20 publications
(22 reference statements)
1
22
0
1
Order By: Relevance
“…For instance, during the phase of dedifferentiation or embryogenic calli generation in E. senticosus and Rosa hybrida, DNA demethylation events are frequent [34], [51]. Recent studies in C. sativa and Acca sellowiana have also showed the importance of demethylation events during SE induction or prior to the start of embryo differentiation [20], [52]. We observed two increases in DNA methylation during the SE of C. canephora (Figure 4A).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…For instance, during the phase of dedifferentiation or embryogenic calli generation in E. senticosus and Rosa hybrida, DNA demethylation events are frequent [34], [51]. Recent studies in C. sativa and Acca sellowiana have also showed the importance of demethylation events during SE induction or prior to the start of embryo differentiation [20], [52]. We observed two increases in DNA methylation during the SE of C. canephora (Figure 4A).…”
Section: Discussionsupporting
confidence: 52%
“…This strongly suggests a rapid cellular response to in vitro conditions [47], [48] accompanied by a drastic chromatin remodeling [49], [50]. Previous reports have shown that embryogenic cell formation is related to the increase of DNA methylation [20], [32], [33]. However, an increase in DNA methylation is not always the condition that has been reported to be important for SE; a decrease in DNA methylation levels seems to be fundamental for embryo development in some species.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In micropropagated Acacia , shoots with juvenile leaves exhibited higher DNA methylation levels than shoots with mature leaves [37]. Transient DNA methylation of ovules accompanied embryogenesis in chestnut [38]. As noted above, in poplar drought stress induced changes in total cellular DNA methylation [30] and was associated with transcriptome changes within separately propagated clones [31].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors described changes at gene transcription level such as DNA methylation or histone modification linked to the embryogenic response [60], somatic embryo maturation [55] and complete somatic embryo development and conversion [37]. Such changes were also observed in the different steps of the cryopreservation procedure [17].…”
Section: Discussionmentioning
confidence: 99%